The Antioxidant Properties of Extracts of Cuscuta spp. Depend on the Parasite and the Host Species - Vanina Lozanova; Denitsa Teofanova; Bilyana Chakarova; Krasimir Rusanov; Kalina Pachedjieva; Anita Tosheva; Tzvetelina Zagorcheva; Lyuben Zagorchev (Antioxidants, 2025)
Dodders (Cuscuta spp.) are prominent parasitic plants widely known and exploited in traditional medicine. They are rich in polyphenolics, which determine their strong antioxidant potential. However, comparatively few of the nearly 200 known species have been characterized for their medicinal potential. In the present study, we aimed to explore the antioxidant potential of four of the most widely distributed Cuscuta species in Bulgaria—C. campestris, C. monogyna, C. epithymum, and C. europaea. They differed significantly in polyphenolic content and accordingly differed in their antioxidant properties, although this correlation is not always straightforward, as shown in C. europaeae. Furthermore, we evaluated the host plant species’ influence on the polyphenolic content, antioxidant properties, and flavonoid profile of C. campestris, finding a significant enhancement when the parasite was grown on aromatic plants—rosemary and thyme—compared to a model host—Arabidopsis thaliana. Seven major flavonoids and phenolic acids—chlorogenic acid, kaempferol-3,7-O-diglucoside, quercetin-3-O-galactoside, kaempferol-3-O-galactoside, quercetin-3-O-glucoside, astragalin, and isorhamnetin-7-glucoside—were annotated after HPLC-MS analysis and found to be affected by the host species. In conclusion, it was found that extracts from different Cuscuta species differ in their antioxidant potential, which the host plants might further modify.